Alternatives to funding scientific research from the viewpoint of Academic Experts at Yemeni University - Humaid, Mohamed Abdullah Hassan; Al-Hamdani, Rajja Mohamed Ahmed (Journal of Educational and Psychological Sciences, 2021)
The current research aimed to identify alternatives to funding scientific research from the point of view of academic experts in Yemeni universities, And the modified Delphi method were used, with the participation of a sample of academic experts in Yemeni universities, In the first round, consisted (34) male and female experts, and in the second round (30) male and female experts, They were chosen in a purposive manner, the questionnaire was used as a research tool, which included (37) items distributed over two axes. The research had several results, the most important of which were: All research axes were given a high degree of importance. The axis of obstacles to funding alternatives for scientific research obtained a high degree, As for the alternatives to funding scientific research, they all got a high degree of importance, The field of other financing alternatives ranked first, the field of self-financing alternatives ranked second, and in the third and last place comes the alternatives to government funding, The research recommended several recommendations, including: Paying attention to scientific research Increasing the share of scientific research from country budget.
Keywords: Alternatives; funding; research; Experts; Yemeni University